Manajemen Administrasi BAZNAS pada Program SDGs di Era Pandemi - Bambang Subahri; Amiruddin Hadi; Ni'mah Lailatul Mas'adah (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2021)
Baznas is govermental institution non-structural which is independent and it has responsibility to the president throught the ministery which has obligation on the management of national zakat. Therefore, within the operational process of the administrative must be implememted professional and adapt the growth era. Based on the context of finding research that examined the program of Sustainable Development Goals (SGDs) concerning to the administrative management such as the payment of Zakat Maal, Infaq and Shodaqoh via e-banking using the application of SIMBA. The research tried to examined the step of strategic management would be done by BAZNAS Jember in Pandemic era and to know the management of adminstrative as the program of SDGs BAZNAS Jember in this Pandemic era. The method of research conducted was qualitative-descriptive. The data collection using deep interview, observation and documentation. And the data analysis was the interactive analysis concists of four related components, namely data collection, reducing, conclusiom. Thus, the reliability of research used triangulation. The resarch revealed that the management of strategy were planning formulation, planning implementation, and evaluation for each planning. The first step was formulate the planning, formulate the SDGs Village and evaluate the planning with the correction of planned program by seeing the target wether achieved or not.